Creating Mobile Games Using Java ME Platform to Put the Fun into Your Mobile Device and Cell Phone - Hamer, Carol (Apress : Imprint: Apress, 2007)
Creating Mobile Games: Using Java ME Platform to Put the Fun into Your Mobile Device and Cell Phone is a practical build-it-yourself mobile Java games book with lots of complete working code and advice: Shows you how to create a basic game and make it a professional one (by adding a pro look-and-feel by writing your own menus or using the open source J2ME Polish, and enabling marketing/billing from your own web site) Demonstrates Wireless Messaging and other optional APIs (using SMS, PIM, File Connection, Bluetooth, and so forth in a multiplayer game) Covers MIDP3.